Membangun Jiwa Kepemimpinan dan Empati Mahasiswa PPG Prajabatan Universitas Negeri Malang Melalui Program Literasi di SMPN 6 Malang (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the implementation of the short story writing literacy program by PPG Preservice students of the State University of Malang and analyze its contribution to strengthening student leadership character and empathy. The research used a qualitative approach with a case study design that was carried out at SMPN 6 Malang for four weeks. The research subjects consisted of 12 PPG students, 30 students, 2 literacy coaches, and 1 school principal. Data was collected through observations, interviews, reflective journals, and documentation, then analyzed thematically to identify patterns of leadership and empathy that emerged during the program. The results of the study show that the implementation of the short story literacy program encourages students to develop three main forms of leadership, namely instructional leadership which is reflected in the ability to manage the classroom and provide direction, transformational leadership that is seen in the motivation and inspiration given to students, and collaborative leadership through cooperation between students and with supervisors. In addition, this program also strengthens student empathy, both in the cognitive dimension through understanding the student's perspective, and in the affective dimension through sensitivity to students' feelings and needs. Supporting factors that contribute to the success of the program include collaboration between students, full support from schools, and students' enthusiasm in literacy activities. The main obstacles faced are the limited implementation time and the lack of literacy support facilities in schools. The conclusion of this study confirms that the short story writing literacy program not only improves students' writing skills, but also plays an important role in shaping the leadership character and empathy of PPG students as prospective professional educators. Thus, literacy can be a strategic medium in strengthening academic competence as well as the social character of prospective teachers.